Bits de inclusão em Sergipe : uma história da educação digital no Comitê para Democratização da Informática (1998-2011) - Nunes, Cristiane Tavares Fonseca de Moraes (2017)
This work investigates the history of the Center for Digital Inclusion (CDI) and his performance in Sergipe. It is a study of a non-governmental organization (NGO), which aimed to promote informal education through so-called Computer and Citizenship Schools (EICs), making use of the computer, with a view to a digital inclusion and, through it the promotion of social change. The EICs, learn computer to gain employment started to unfold in other actions, involving mobilization and organization around the claim of public policies to guarantee the rights of the communities in which the CDI has been inserted. The research covers the period from 1998, when the CDI activities started in Sergipe, until 2011, when the NGO has stopped working in the state. The study was guided by oral history procedures, in which interviews were conducted with actors involved in the construction of CDI Sergipe. In addition, the research used various documents, such as accounting records, monographs, journals, proceedings, the education program, textbooks and teaching materials prepared by the NGO itself. All this material was considered "document / monument" and thus as suggested by Jacques Le Goff, were questioned, deconstructed and thought of as elements to produce a reflection on the trajectory of CDI.